Comparative study of ropivacaine versus dexmedetomidine-ropivacaine combination in transversus abdominis plane block for postoperative pain control in plastic surgery patients undergoing abdominoplasty - Jan, Summaira; Ahmad, Tawheed; Rashid, Saima (International Surgery Journal, 2019)
Background: Requirement of postoperative analgesic medication is decreased by the use of regional nerve blocks. Transversus abdominis plane (TAP) block is an effective way to provide postoperative analgesia in abdominal surgeries. TAP block using ropivacaine alone has not been consistently proven to be effective in alleviating pain after abdominal surgeries. The objective of the study was to compare the combination of dexmedetomidine and ropivacaine to ropivacaine alone in TAP block for abdominoplasty patients. Time to onset of post-operative pain and time interval for need of rescue analgesia were compared. Methods: Sixty ASA (American Society of Anesthesiology) grade I or II patients undergoing abdominoplasty were allocated to two groups with thirty patients in each group. In this randomized, controlled, double-blinded study, the test group received TAP block using 20 ml (100 mgs) 0.5 percent of ropivacaine mixed with 50 µg of dexmedetomidine while as Control group received TAP block with 20 ml (100 mgs) of 0.5 percent of ropivacaine alone. Patient demographics, time to initial reporting of post-operative pain, time to need of first rescue analgesia, quality of pain block and side effects were recorded. Results: Time to initial onset of pain and time to need of first rescue analgesia were significantly longer in the test group than control group. The two groups were similar in demographics and quality of pain block, with no significant difference in side effects. Conclusions: Addition of dexmedetomidine to ropivacaine for TAP block in abdominoplasty patients prolong the time to initial onset of pain and time to need for first rescue analgesia.